Environmental Emissions - Viskup, Richard (IntechOpen, 2021)
Today, the issue of environmental emissions is more important than ever before. Air pollution with particulates, soot, carbon, aerosols, heavy metals, and so on is causing adverse effects on human health as well as the environment. This book presents new research and findings related to environmental emissions, pollution, and future sustainability. Written by experts in the field, chapters cover such topics as health effects, emission monitoring and mitigation, and emission composition and measurement.